High throughput selection of effective serodiagnostics for Trypanosoma cruzi infection. - Gretchen Cooley; R Drew Etheridge; Courtney Boehlke; Becky Bundy; D Brent Weatherly; Todd Minning; Matthew Haney; Miriam Postan; Susana Laucella; Rick L Tarleton (Public Library of Science (PLoS), 2008)
Diagnosis of Trypanosoma cruzi infection by direct pathogen detection is complicated by the low parasite burden in subjects persistently infected with this agent of human Chagas disease. Determination of infection status by serological analysis has also been faulty, largely due to the lack of well-characterized parasite reagents for the detection of anti-parasite antibodies.In this study, we screened more than 400 recombinant proteins of T. cruzi, including randomly selected and those known to be highly expressed in the parasite stages present in mammalian hosts, for the ability to detect anti-parasite antibodies in the sera of subjects with confirmed or suspected T. cruzi infection.A set of 16 protein groups were identified and incorporated into a multiplex bead array format which detected 100% of >100 confirmed positive sera and also documented consistent, strong and broad responses in samples undetected or discordant using conventional serologic tests. Each serum had a distinct but highly stable reaction pattern. This diagnostic panel was also useful for monitoring drug treatment efficacy in chronic Chagas disease.These results substantially extend the variety and quality of diagnostic targets for Chagas disease and offer a useful tool for determining treatment success or failure.